Problem from hell : America and the age of genocide America and the age of genocide - Power, Samantha (New York : Harper Perennial, 2007)
Winner of the 2003 Pulitzer Prize For General Nonfiction National Book Critics Circle Award Winner In her award-winning interrogation of the last century of American history, Samantha Power -- a former Balkan war correspondent and founding executive director of Harvard's Carr Center for Human Rights Policy -- asks the haunting question: Why do American leaders who vow "never again" repeatedly fail to stop genocide? Drawing upon exclusive interviews with Washington's top policy makers, access to newly declassified documents, and her own reporting from the modern killing fields, Power provides the answer in "A Problem from Hell" -- a groundbreaking work that tells the stories of the courageous Americans who risked their careers and lives in an effort to get the United States to act.
"Race murder" -- "Crime without a name" -- Crime with a name -- Lemkin's law -- "Most lethal pair of foes" -- Cambodia : "helpless giant" -- Speaking loudly and looking for a stick -- Iraq : "human rights and chemical weapons use aside" -- Bosnia : "no more than witnesses at a funeral" -- Rwanda : "mostly in a listening mode" -- Srebrencia : "getting creamed" -- Kosovo : dog and a fight -- Lemkin's courtroom legacy -- Conclusion -- Notes -- Bibliography -- Acknowledgments -- Index.
Reprint with a new postscript. Originally published: New York : Basic Books, 2002.
Includes bibliographical references (p. [583]-597) and index.
Keywords: Genocide -- History -- 20th century; Genocide -- History; United States -- Foreign relations -- 20th century; United States -- Foreign relations